IMPLEMENTASI EKONOMI SIRKULAR BUDIDAYA TANAMAN PADI PADA KELOMPOK TANI SOPONYONO I DI DESA TANAH PRIUK KABUPATEN MUSI RAWAS - Safriyani, Etty; Murniati, Nely; Karyono, Teguh (Gapenas Publisher, 2024)
Circular economy is a circular system by maximizing the added value of waste materials that are not used in one production activity. One of circular economy in rice cultivation is integrated rice-duck-azolla farming. This concept produces a mutually beneficial agro-ecosystem between rice, ducks and azolla. Rice plants create a good growing environment for ducks and azolla. Duck droppings are a source of nutrients for azolla and rice plants and ducks are pest and weed control for rice plants. Azolla is a source of organic nitrogen and weed control for rice plants and a source of feed for ducks. This community service activity AIMS to reduce dependence on agrochemicals in rice cultivation and reduce the use of commercial feed in duck cultivation. The activity was carried out at the soponyono 1 farmer group, tanah periuk village, muara beliti district, musi rawas regency, south sumatera from july to september 2024. The results shows that the activity that utilize rice-duck-azolla cultivation, process azolla into compost and duck feed and process duck eggs. The sustainability of the program can be seen from the use of compost for ipomoea aquatica and spinach cultivation as well as feed given to duck